Prevalence of helminth parasites in sheep (Ovis aries) in Tangail district, Bangladesh (Journal of the Bangladesh Agricultural University, 2013)
Prevalence of helminths of sheep in relation to age, sex, nutritional status, management system and flock size was studied at Tangail district, Bangladesh from July to December 2010 by fecal examination. A total of 190 sheep were examined of which 154 (81.1%) were positive for one or more species of helminth parasites. Seven species of helminths were identified, of them three species were trematodes, namely, Fasciola gigantica (8.4%), Paramphistomum spp. (44.2%) and Schistosoma indicum (3.7%); four species were nematodes, namely, Bunostomum sp (19.0%), Trichuris spp. (2.1%), Strongyles (62.6%) and Strongyloides spp. (9.5%). No cestodes were identified. Prevalence of helminths was significantly (p1-2 year (92.7%) than adult aged > 2 years (83.3%) and lamb aged ? 1 year (63.6%). Higher prevalence was recorded in female than in male sheep. In relation to nutritional status and flock size, prevalence of helminths were significantly (p